Analisa Perbandingan Rencana Anggaran Biaya Pekerjaan Pelat Lantai Bondek Antara Lantai 1,2,3 dan 4 pada Pembangunan Gedung Pelayanan - Djawa, Norberth Randa ; Suhudi ; Wijaya , Handika Setya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The world of construction in Indonesia is growing rapidly to help meet people's needs, give them comfort, and help them to have advanced prosperity. For this reason, the number of construction projects currently in progress is large, so engineers must pay attention to having good quality construction. To get good quality construction results, there are three aspects that must be considered: cost, quality, and time. the three aspects are very high, especially related to the cost aspect. A good, accurate, and efficient budget plan is reflected in the good results of the project. An efficient budget plan will not only make the project successful, but will also benefit the engineer. Before starting a project, the engineer needs to make a budget plan, the first is the Cost Budget Plan (RAB). Therefore, the authors analyze the Permen PU 28 / PRT / M / 2016 budget plan for the work of the integrated service building building of the tribhuwana tunggadewi malang university. In this analysis, the Budget Plan (RAB) based on Minister of Public Works Regulation 28 / PRT / M / 2016 is Rp 485,094,171